Original paperAdministration of leukemia inhibitory factor increases Opalin and myelin oligodendrocyte glycoprotein expression in the cerebral cortex in a cuprizone-induced model of demyelination - Mashayekhi, Farhad; Hadiyan, Sara Pishgah; Salehi, Zivar (Folia Neuropathologica, 2015)
Multiple sclerosis (MS) lesions are characterized by inflammatory demyelination and reactive gliosis, and although remyelination occurs in some lesions it is limited and incomplete. Leukemia inhibitory factor (LIF) is an important cytokine that stimulates oligodendrocyte proliferation and survival in vitro . Opalin is a unique molecular marker for mature oligodendrocytes. The aim of this study was to demonstrate the role of LIF on Opalin and myelin oligodendrocyte glycoprotein (MOG) expression in the cerebral cortex of cuprizone-induced MS mice. The mice were treated with cuprizone for five weeks in order to induce MS. The mice were then divided into 3 groups. The first group was injected intraperitoneally (IP) with LIF for six weeks in the amount of 30 µg/kg bw per day. The second group (SHAM) was injected IP with normal saline and the third group was left without injection as a control. After six weeks the mice were killed, the cerebral cortex was harvested, and the expression of MOG and Opalin was studied. Using western blotting we found that LIF increases Opalin and MOG expression in the cerebral cortex extracts as compared to SHAM and control groups. However, no significant difference in the Opalin and MOG expression was seen between SHAM and control groups. It is concluded that LIF may have an important role in the process of remyelination by increasing Opalin expression and MOG expression.